"Doulas shouldn't be considered visitors, we should be considered a part of [the] team": doula care in Georgia, USA during the COVID-19 pandemic. Issue 1 (31st December 2022) - Turner, Daria; Lindsey, Alyssa; Shah, Priya; Sayyad, Ayeesha; Mack, Amber; Rice, Whitney S.; Mosley, Elizabeth A.
Abstract: Doula support improves maternal-child health outcomes. However, during the COVID-19 pandemic, hospitals restricted the number of support people allowed during childbirth. An academic-community research team conducted 17 in-depth interviews and structured surveys with doulas in metro-Atlanta, Georgia, USA from November 2020 to January 2021. Surveys were analysed for descriptive statistics in Stata v. 14, and interviews were analysed in Dedoose using a codebook and memo-ing for thematic analysis. All 17 doulas reported COVID-19 changed their practices: most were unable to accompany clients to delivery (14), started using personal protective equipment (13), used virtual services (12), and had to limit the number of in-person prenatal/postpartum visits (11). Several attended more home births (6) because birthing people were afraid to have their babies in the hospital. Some stopped seeing clients altogether due to safety concerns (2). Many lost clientele who could no longer afford doula services, and some offered pro bono services. Most doulas pointed to restrictive hospital policies that excluded doulas and disallowed virtual support as they felt doulas should be considered a part of the team and clients should not be forced to decide between having their doula or their partner in the room. COVID-19 has severely impacted access to and provision of doula care, mostly due to economic hardship for clients and restrictive hospital policies. At the same time, doulas and their clients have been resourceful – using virtual technology, innovative payment models, and home births.